2008
DOI: 10.1590/s1519-69842008000200015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of algal densities on the toxicity of chromium for Ceriodaphnia dubia Richard (Cladocera, Crustacea)

Abstract: Food availability may affect metal toxicity for aquatic organisms. In the present study, the influence of high, medium and low densities of the algae Pseudokirchneriella subcapitata (10 6 , 10 5 and 10 4 cells.mL -1, respectively) on the chronic toxicity of chromium to the cladoceran Ceriodaphnia dubia was investigated. C. dubia was exposed to a range of chromium concentration from 2.71 to 34.04 mg.L -1 and fed with algae at various densities. In another experiment, the green alga was exposed to chromium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…This might be due to essentiality of Cu towards crustaceans. Present study shows that chromium is more toxic than copper as also reported for different crustaceans (Guilhermino et al, 2000;Rodgher and Espíndola, 2008;Rajaretnam and Stanley, 2015).…”
Section: Results and Discussion:-supporting
confidence: 86%
“…This might be due to essentiality of Cu towards crustaceans. Present study shows that chromium is more toxic than copper as also reported for different crustaceans (Guilhermino et al, 2000;Rodgher and Espíndola, 2008;Rajaretnam and Stanley, 2015).…”
Section: Results and Discussion:-supporting
confidence: 86%
“…The toxicity of these metals on zooplankton can be detected at multiple levels of biological organization, from suborganismal (molecular) to ecosystem level. Thus, chromium and cadmium metals are known to interfere with biochemical activity of the enzymes acetylcholinesterase and glutathione S‐transferase (Guilhermino et al,; Diamantino et al,; Barata et al,), to decrease the reproduction and survival of individual species (Seco‐Gordillo et al,; Brooks et al,; Rodgher and Espíndola,b), negatively affect population growth rates (Coniglio and Baudo,; Heugens et al,) and, in the case of the cadmium, can be biomagnified in the trophic chain (Reinfelder et al,; Ruangsomboon and Wongrat,).…”
Section: Introductionmentioning
confidence: 99%
“…Kitana and Callard (2008) Toxicity of Chromium. Rodgher and Espindola (2008b) reported that the density of the green algae, concentrations of calcium in hemolymph, suggesting that impairment of calcium uptake and homeostasis may serve as a mechanism of toxicity.…”
Section: Biomarkers Of Metals Contamination Daphniamentioning
confidence: 99%